2011
DOI: 10.18357/ijcyfs21/220115429
|View full text |Cite
|
Sign up to set email alerts
|

The Over-Representation of Children in Care in the Youth Criminal Justice System in British Columbia: Theory and Policy Issues

Abstract: Placement in child protection services, or becoming a child in care, is associated with a disproportionate involvement in youth and adult criminal justice systems. While there is not extensive research on this relationship, there is evidence that many children in care have risk profiles consistent with criminal justice involvement. This article provides an overview of the prevalence of exposure to risk factors related to mental health, education, and antisocial behaviour among children in care, in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Although foster care is not a latent trait, it is a social factor that may be a proximal indicator of an underlying propensity to offend. This may be further supported by the higher prevalence of disruptive behavior among foster care youth as can be inferred by higher rates of fetal alcohol spectrum disorder (FASD) and attention deficit hyperactivity disorder (ADHD) as compared to non-foster care youth (Corrado et al, 2011;Ouyang et al, 2008). Both FASD and ADHD have been linked with more stable characteristics such as low self-control and deficits in executive functioning and thus could underlie the effects of foster care placement on offending.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although foster care is not a latent trait, it is a social factor that may be a proximal indicator of an underlying propensity to offend. This may be further supported by the higher prevalence of disruptive behavior among foster care youth as can be inferred by higher rates of fetal alcohol spectrum disorder (FASD) and attention deficit hyperactivity disorder (ADHD) as compared to non-foster care youth (Corrado et al, 2011;Ouyang et al, 2008). Both FASD and ADHD have been linked with more stable characteristics such as low self-control and deficits in executive functioning and thus could underlie the effects of foster care placement on offending.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factor profiles of youth that have experienced child welfare intervention are more concerning than similar youth who never have been placed in care (Corrado et al, 2011;Cutuli et al, 2016). It is possible that one of these risk factors that are disproportionately found among foster care youth aggravates the negative effects of foster care placement or it may be demonstrated that foster care placement is unrelated to offending in the absence of these other risk factors (Yang et al, 2017).…”
Section: Risk Factor Candidates For Moderating the Foster Care-offendmentioning
confidence: 99%
“…A key theoretical and policy issue was whether these disproportionate involvements of Aboriginal young people in Canadian youth criminal justice reflected either discrimination, or their higher prevalence of risk factors for serious offending and more serious offence profiles compared to non-Aboriginal young offenders. Regarding the latter explanation, Aboriginal young offenders were disproportionately characterized by inter-related individual and environmental risk factors that have been commonly identified as correlates of youth offending, including high levels of poverty; family conflict; lower levels of education; substance abuse problems; and psychological and emotional problems (Corrado and Cohen, 2002; Corrado et al, 2011). In addition, Aboriginal people were three times more likely than non-Aboriginal people to experience violent victimization and higher incidents of physical and sexual abuse, particularly from relatives, friends, neighbours or acquaintances (Bateman, 2011; Brzozowski et al, 2006).…”
Section: Aboriginal Offenders and Canada’s Youth Justice Systemmentioning
confidence: 99%
“…However, rates of childhood poverty in Canada have not decreased since the 1950s (Campaign 2000; Family Services Toronto, 2014; Statistics Canada, 2009), current waiting times to see a child psychiatrist are typically several months (Kowalewski, McLennan, & McGrath, 2011) and many children are never referred for assessment (Sayal, 2006; Waddell, McEwen, Shepherd, Offord, & Hua, 2005), child welfare systems are overburdened and underresourced (Blackstock, Cross, George, Brown, & Formsma, 2006), and the intergenerational impacts of colonization on Indigenous populations have not been properly addressed (Truth and Reconciliation Commission of Canada, 2015). Criminal justice systems across the country are repositories for individuals who come from disadvantaged childhoods (Corrado, Freedman, & Blatier, 2011; Corrado, Kuehn, & Margaritescu, 2014); prisoners living with mental illness and FASD make up a notable percentage of this population (Burd et al., 2003; Centre for Addiction and Mental Health, 2013; Fast et al., 1999; MacPhail & Verdun-Jones, 2013; Popova et al., 2011); and Indigenous peoples are overrepresented (Corrado et al., 2014; Cunneen, 2014). Canada lacks a national strategy aimed at improving prison and postincarceration supports and services for prisoners living with mental illness, addictions, and cognitive deficits, despite research indicating the substantial human, financial, and societal gains that can be made with better coordination of policies and services (Centre for Addiction and Mental Health, 2013).…”
Section: Discussionmentioning
confidence: 99%